Bibliometric Mapping of Local Knowledge Preservation: Connection to Information Literacy and Open Science - Mayang Rumaisha Nur Fauziyah; Damayani Ninis Agustini; Erwina Erwina (Indonesian Journal of Librarianship, 2025)
Abstract Problem Statement: Preserving local knowledge has become a critical effort in this era of globalization to safeguard cultural values and traditions threatened by modernization. In general, local knowledge plays a strategic role in natural resource management, environmental conservation, and sustainable social development. Purpose: this research aims to analyze developments in the field of local knowledge preservation, document relevant international publications, and identify research positions on the enhancement of information literacy and open science. Method: . A descriptive quantitative approach was used with bibliometric analysis. Data were retrieved from the Scopus database for the period 2014–2024. Result: The results showed that research on local knowledge preservation primarily focuses on biodiversity conservation, natural resource management, and community empowerment. However, the explicit connection between local knowledge preservation and information literacy or open science remains underdeveloped. This indicates that local knowledge preservation has significant potential to strengthen information literacy and support open science, but the strategic integration requires further development. Conclusion: The results provide an overview of global research trends and show opportunities to incorporate local knowledge into future information systems that are more inclusive and accessible.